The rule of law principle in the constitutional case law of the former communist countries: the decisions on transitional justice and european integration - Di Gregorio, Angela (Journal of the Belarusian State University. Law, 2019)
The purpose of this paper is to check how the rule of law principle is interpreted in the constitutional case law of the Central and Eastern European Members of the European Union. The goal of this research is twofold. First, these are countries that have experienced a communist past, during which the conception of the rule of law, although not absent, assumed different contents compared to those typical of the Western legal tradition. Second, a survey on the jurisprudential interpretation of the main constitutional values, in this case the rule of law, helps to clarify the cultural and value context of these countries. Considering the heavy rule of law crisis, which took place in Hungary and Poland in recent years, this recognition is particularly important in order to avoid cumulative judgments that could devalue the former communist countries in general, trivializing the harsh path of democratic conditionality that has assisted them in the European application process.